Evaluation of tenascin expression in ameloblastoma, odontogenic keratocyst, and dentigerous cyst by immunohistochemistry - Narges Ghazi; Nasrollah Saghravanian; Majid Mirhashemi; Abolfazl Abedini Ardakani (Advanced Biomedical Research, 2023)
Background: The aim of this study was to evaluate the expression pattern of tenascin in ameloblastoma, odontogenic keratocyst, and dentigerous cyst. Materials and Methods: The expression of tenascin was evaluated in microscopic slides of 42 paraffin blocks including 12 ameloblastomas, 15 odontogenic keratocysts, and 15 dentigerous cysts by immunohistochemistry. The expression of tenascin was examined in stroma, epithelium-connective tissue interface, and epithelium of the lesions by two pathologists semiquantitatively. Results: Stromal expression of tenascin was higher in ameloblastomas than other groups. All the paired groups showed significant differences except comparison of odontogenic keratocysts and dentigerous cysts. Epithelial-mesenchymal interface expression of tenascin was significantly higher in ameloblastomas and odontogenic keratocysts than dentigerous cysts. All the paired groups showed significant differences except comparison of odontogenic keratocysts and ameloblastomas. Expression of tenascin in epithelial cells of ameloblastomas was focal whereas in odontogenic keratocysts and dentigerous cysts negative immunoreactivity was reported. Conclusions: Expression of tenascin in these lesions suggests that it could play a role in epithelial-mesenchymal interaction. Higher expression of tenascin in ameloblastoma, can explain immaturity of its stroma and aggressive nature of this lesion compared with other studied groups. Moreover, higher expression of tenascin in epithelial-mesenchymal interface of odontogenic keratocyst compared with dentigerous cyst reveals its more immature and aggressive nature and high rate of recurrence.